Echo-Guided Insertion of a Dual-Lumen Cannula for Venovenous Extracorporeal Membrane Oxygenation. Issue 4 (May 2019) - Cianchi, Giovanni; Lazzeri, Chiara; Bonizzoli, Manuela; Batacchi, Stefano; Peris, Adriano
Abstract : We provide a step-by-step description of the insertion of a dual-lumen cannula, for venovenous extracorporeal membrane oxygenation support and how a close monitoring by combined transthoracic and transesophageal techniques ensures a safe procedure and can promptly detect complications. Abstract : Supplemental Digital Content is available in the text.